Simulation and Serious Games for Education - Cai, Yiyu.; Goei, Sui Lin.; Trooster, Wim.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book introduces state-of-the-art research on simulation and serious games for education. The major part of this book is based on selected work presented at the 2014 Asia-Europe Symposium on Simulation and Serious Games held in Windesheim University of Applied Sciences, the Netherlands (Oct 1-2, 2014). It covers three major domains of education applications that use simulation and serious games: Science, Technology, Engineering and Mathematics (STEM) Education; Special Needs Education and Humanity and Social Science Education. Researchers and developers in simulation and serious games for education benefit from this book, and it also offers educators and professionals involved in training insights into the possible applications of simulation and serious games in various areas.
Virtual Pink Dolphins Project: An International Effort for Children with Autism in Special Needs Education -- A Germ for Young European Scientists: Drawing-Based Modeling -- Virtual Reality Enabled Intravascular Catheterization Simulation -- Simulation-enabled Vocational Training for Heavy Crane Operations -- Formative evaluation of a mathematics game for out-of-school children in Sudan -- Empowering Vocational Math Teachers Using Digital Learning Materials With Workplace Assignments -- The Odyssey Game -- Social Development for Children with Autism using Kinect Gesture Games: A Case Study in Suzhou Industrial Park Renai School -- The Effectiveness of the Game LINGO Online: A Serious Game for English Pronunciation -- Looking into eyes: a gaze tracking system for children with autism spectrum disorders.
Keywords: Computational intelligence; Educational technology; User interfaces (Computer systems).; Human-computer interaction; School Psychology; Computational Intelligence; Digital Education and Educational Technology; User Interfaces and Human Computer Interaction; School Psychology